Analysis of the Influence of Debt to Asset Ratio (DAR) on Return on Assets (ROA) at PT Bank Central Asia Tbk for the 2020-2024 Period - Hapsari, Caecilia Niken; Marciano, Christian; Manurung, Elizabeth Tiur (Universitas Mohammad Husni Thamrin, 2025)
This study aims to analyze the effect of the Debt to Asset Ratio (DAR) on Return on Assets (ROA) at PT Bank Central Asia Tbk during the 2020–2024 period. The research is motivated by the importance of maintaining a balance between funding structure and profitability performance, particularly during the post-pandemic economic recovery period. DAR is employed as a solvency indicator that reflects the proportion of assets financed by liabilities, while ROA serves as a key profitability indicator measuring management’s effectiveness in generating profits from total assets. This research adopts a quantitative associative approach and utilizes secondary data derived from the annual financial statements of PT Bank Central Asia Tbk over a five-year period. The data are analyzed using simple linear regression, supported by the coefficient of determination and partial significance testing (t-test) to assess the influence of the independent variable on the dependent variable. The results indicate that the Debt to Asset Ratio has a negative relationship with Return on Assets, suggesting that a decrease in leverage is associated with an improvement in asset profitability. The regression results reveal a negative DAR coefficient, confirming an inverse relationship between the two variables. Although the coefficient of determination indicates that DAR explains a substantial portion of ROA variation, the statistical test results show that the effect is not statistically significant due to the limited number of observations. Overall, the findings suggest that prudent capital structure management plays an important role in supporting the profitability performance of PT Bank Central Asia Tbk during the research period.